Dokumenty Soborów Powszechnych. Tekst grecki, łaciński, polski, układ i opracowanie ks. Arkadiusz Baron - ks. Henryk Pietras SJ, Wydawnictwo WAM, t. 1: 325-787, ŹMT 24, Kraków 2001, ss. 400; t. 2: 869-1312, ŹMT 26, Kraków 2002, ss. 680. - Figiel, Józef (Vox Patrum, 2003)
review